If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -7 = 7x + -3 Reorder the terms: -7 + 9x = 7x + -3 Reorder the terms: -7 + 9x = -3 + 7x Solving -7 + 9x = -3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -7 + 9x + -7x = -3 + 7x + -7x Combine like terms: 9x + -7x = 2x -7 + 2x = -3 + 7x + -7x Combine like terms: 7x + -7x = 0 -7 + 2x = -3 + 0 -7 + 2x = -3 Add '7' to each side of the equation. -7 + 7 + 2x = -3 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = -3 + 7 2x = -3 + 7 Combine like terms: -3 + 7 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| 3z-z=0 | | 2x+1=-x+10 | | -3_x-4/-54= | | x+2.2=9.5 | | 28=72 | | 3x+4y=9.10 | | 2x^4-6x^3-8x-3=0 | | 2.5n+1= | | 5(3x-1)=4(4x-3) | | 200=.024*X+(-125) | | 1.6x+(3x-7)=4x+(4x-1) | | -7+22=m-7 | | 4(x+5)-14=30 | | 9x-1=41-5x | | =2rs+14r | | X=9.4+-0.8y | | X=9.4+-0.8 | | 8(11/8)-7/7 | | 6x-7=3-9x | | -2x+5x-10=20 | | 3x+y+3=0 | | 8(7/8)-7/7 | | 8(9/8)-7/7 | | ln(3x+5)=20 | | 8(1)-7/7 | | 5x+5y-7y= | | Cos(2t)=0.8 | | 9x-5x+8-3=7x+13-5x-2 | | 8(5/4)-7/7 | | ln(x+3)=14 | | 3x-5+4=16 | | 5*r=0 |